2003
DOI: 10.1179/003258903225008517
|View full text |Cite
|
Sign up to set email alerts
|

Microstructure, mechanical properties and tribological behaviour of PM Fe-Cu-Zn alloys containing solid lubricants

Abstract: properties. One of the important requirements for materials used in bearing production is the coeYcient of friction.4 Fe-Cu-Zn alloys containing solid lubricants of Generally the coeYcient of friction is highly dependent on graphite and talc produced via cold pressing and the compositions used. sintering technology are investigated. The in uence Many of the early works were focused on the study and of composition and sintering temperature on open optimisation of bronze alloys because of the potentially large p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
4
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
4
1
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(4 citation statements)
references
References 0 publications
0
4
0
Order By: Relevance
“…After the test, the yield strength, tensile strength, fracture strength and ductility were measured and fracture surfaces were examined using the inverted microscope. Increase in yield strength and decrease in tensile elongation can be achieved by decreasing the thickness of the specimen, as has been investigated on Cu, Al, Au and Ni foils with thickness less than 250 µm [16,17]. From the literature survey and experimental observation, it was found that the tensile properties of specimens depend on the annealing temperature as well as time, and by increasing any one of these, the tensile strength normally reduces and ductility increases.…”
Section: Tensile Testmentioning
confidence: 99%
“…After the test, the yield strength, tensile strength, fracture strength and ductility were measured and fracture surfaces were examined using the inverted microscope. Increase in yield strength and decrease in tensile elongation can be achieved by decreasing the thickness of the specimen, as has been investigated on Cu, Al, Au and Ni foils with thickness less than 250 µm [16,17]. From the literature survey and experimental observation, it was found that the tensile properties of specimens depend on the annealing temperature as well as time, and by increasing any one of these, the tensile strength normally reduces and ductility increases.…”
Section: Tensile Testmentioning
confidence: 99%
“…Previous studies have also shown that the microstructure and mechanical properties of brass can also be enhanced with a carefully balanced composition of Cu-Zn and other alloying elements, addition of additives as well as the use of appropriate heat treatment technique [17][18]. Many innovative approaches aimed at improving the microstructure and mechanical properties of brass alloy have been reported [19][20][21]. For instance, Imai et al [22] reported that the strength of Cu-Zn alloy (brass alloy) can be improved via the addition of small amount of chromium in solid solution as the strength impact of Cr solid solution in Cu-Zn alloy was reportedly significant as opposed to brass alloy strengthening via Cr precipitation.…”
Section: Introductionmentioning
confidence: 99%
“…Addition of 0.6 % Carbon yielded a tensile strength of 275-500 MPa and transverse rupture strength of 640-1260 MPa [10]. Addition of Brass 10 % with iron plays a major role in determining the mechanical properties and microstructure with an optimum sintering temperature less than or equal to 1000 °C [11]. Addition of Cu, C, and Sn with iron powder improves the mechanical and microstructure property.…”
Section: Introductionmentioning
confidence: 99%